Construction of New Ion Selective Electrodes for Determination Fe(III) and Their Application in Pharmaceutical samples - Baghdad Science Journal (مجلة بغداد للعلوم, 2013)
Liquid membrane electrodes for the determination iron(III) were constructed based on chloramphenicol sodium succinate and iron(III) CPSS-Fe(III) as ion pair complex, with four plasticizers Di-butyl phosphate (DBP); Di-butyl phthalate (DBPH); Di-octyl phthalate (DOP); Tri-butyl phosphate (TBP); in PVC matrix . These electrodes give Nernstian and sub-Nernstian slopes (19.79, 24.60, 16.01 and 13.82mV/decade) and linear ranges from (1x10-5-1x10-2 M, 1x10-5-1x10-2 M, 1x10-6-1x10-2 M and 1x10-5-1x10-2 M) respectively. The best electrode was based on DBP plasticizer which gave a slope 19.79 mV/decade, correlation coefficient 0.9999, detection limit of 9×10-6 M, lifetime 37 day displayed good stability and reproducibility and used to determine iron(III) in pharmaceutical samples. The selectivity coefficient interferences of (K+, Na+, Cu+2, Mn+2, Zn2+, Al3+,Folic acid) were studied using separate and mixed methods for selectivity coefficient determination. The pH and life time of the electrodes were also studied.